Analisis Kerentanan Keamanan pada Website Kelurahan Rimba Sekampung dengan Menggunakan Framework OWASP ZAP - Nurasmawati, Nurasmawati; Mansur, Mansur; Hidayasari, Nurmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The security of web-based applications is increasingly important due to evolving cyber threats. This study analyzes the security vulnerabilities of the Kelurahan Rimba Sekampung website using the OWASP ZAP tool to identify potential weaknesses and recommend mitigation strategies. The methodology includes automated scanning, vulnerability analysis, and applying security improvements. The initial scan identified 15 vulnerabilities, including issues under Broken Access Control, Security Misconfiguration, Cryptographic Failures, Use of Vulnerable and Outdated Components, and Software and Data Integrity Failures. After implementing mitigation measures, the number of vulnerabilities was reduced to 12. Key improvements included strengthening the Content Security Policy (CSP), enhancing encryption mechanisms, and configuring HTTP headers and cookies correctly. These actions significantly reduced the website’s security risks. The results of this study can serve as a reference for web administrators in enhancing application security and safeguarding user data.